1993
DOI: 10.22358/jafs/69861/1993
|View full text |Cite
|
Sign up to set email alerts
|

The energy and protein value of double-low rape seeds for growing pigs

Abstract: Groups of 12 growing Landrace pigs with an average body weight of 55 ± 1.5 kg were fed a diet containing from 5 to 30% (Expt. 1) or 0 to 25% (Expt. 2) raw rape seeds. The digestibility of the diet was determined by either the indicator method (Expt. 1) or total collection method (Expt. 2). Metabolizability of energy was also determined in experiment 2. The apparent digestibility of crude protein was not dependent on the proportion of rape seeds in the diet, whereas the digestibility and metabolizability of ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…It may be that the seeds used for the production of the RSM-24 contained more glucosinolates than allowed by Polish standards (30 /mioles/g fat-free DM) for double low rapeseed varieties. This supports the results of Raj et al (1993) who found four times more glucosinolates in seeds than in the extracted oil meal (22.5 and 5.5 ^moles/g fat-free dry matter, respectively). Experiment 1.…”
Section: Resultssupporting
confidence: 92%
“…It may be that the seeds used for the production of the RSM-24 contained more glucosinolates than allowed by Polish standards (30 /mioles/g fat-free DM) for double low rapeseed varieties. This supports the results of Raj et al (1993) who found four times more glucosinolates in seeds than in the extracted oil meal (22.5 and 5.5 ^moles/g fat-free dry matter, respectively). Experiment 1.…”
Section: Resultssupporting
confidence: 92%